"Inverted" porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111). Issue 58 (6th July 2017) - Lepper, Michael; Köbl, Julia; Schmitt, Tobias; Gurrath, Martin; de Siervo, Abner; Schneider, M. Alexander; Steinrück, Hans-Peter; Meyer, Bernd; Marbach, Hubertus; Hieringer, Wolfgang
Abstract : Peculiar "inverted" intramolecular conformation of a free-base porphyrin due to specific attractive molecule–substrate interaction. Abstract : Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted" adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a well-studied system, shedding light on the peculiar molecule–substrate interaction and the resulting intramolecular conformation.